Quality and timber value of European larch (Larix decidua Mill.) trees in the Karavanke region - Kadunc, Aleš (Zbornik gozdarstva in lesarstva, 2011)
Although European larch is a commercially important tree species in the Alps, this study is among the first focusing on the quality and value of larch trees. Data from permanent sample plots of the Slovenia Forest Service (802 plots; 1851 trees) was used to model the quality and value of standing larch trees. The share of excellent and very good quality timber amounted to 49%, but the share of veneer logs and sawlogs I was only 11.7%. The quality and value of larch trees were positively influenced by the diameter at breast height and stand basal area, and negatively by altitude and harvesting intensity. In addition, timber value was higher in stands in regeneration and uneven-aged stands and in stands with a low share of spruce or high share of deciduous tree species. Trees from higher social layers and undamaged trees also proved to have more valuable timber. The quality of larch trees was lower on extreme beech and pine forest types.
Keywords: evropski macesen; kvaliteta; Larix decidua; multivariantna analiza